2013
DOI: 10.1371/journal.pone.0058232
|View full text |Cite
|
Sign up to set email alerts
|

PINCH in the Cellular Stress Response to Tau-Hyperphosphorylation

Abstract: Particularly interesting new cysteine- histidine- rich protein (PINCH) is an adaptor protein that our data have shown is required for neurite extension under stressful conditions. Our previous studies also report that PINCH is recalled by neurons showing decreased levels of synaptodendritic signaling proteins such as MAP2 or synaptophysin in the brains of human immunodeficiency virus (HIV) patients. The current study addressed potential role(s) for PINCH in neurodegenerative diseases. Mass spectrometry predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 44 publications
(58 reference statements)
7
39
0
Order By: Relevance
“…Distinct PINCH bands were detected at approximately 55 and 71 kDa (Figure 1A), as previously reported [4, 6]. A third PINCH immunoreactive band was detected at approximately 84 kDa in some cases, reminiscent of the approximate size detected by immunoprecipitation of PINCH and hpTau [6].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Distinct PINCH bands were detected at approximately 55 and 71 kDa (Figure 1A), as previously reported [4, 6]. A third PINCH immunoreactive band was detected at approximately 84 kDa in some cases, reminiscent of the approximate size detected by immunoprecipitation of PINCH and hpTau [6].…”
Section: Resultssupporting
confidence: 85%
“…Our results suggest that changes in CSF levels of PINCH correlate with CSF hpTau levels in this cohort of HIV participants. Previous studies reported that PINCH and hpTau bind one another both in vitro , in vivo and in the brains and CSF of HIV patients [6]. Our earlier studies also reported higher levels of PINCH in brain and CSF in both HIV with no CNS alterations and HIVE, compared to HIV negative adults.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations